Positive effects of lignocellulose on the formation and stability of aerobic granular sludge - Xu, Jie; Gao, Yuan; Bi, Xuejun; Li, Lin; Xiang, Wenjuan; Liu, Shichang (Frontiers in Microbiology, 2023)
Lignocellulose is one of the major components of particulate organic matter in sewage, which has a significant influence on biological wastewater treatment process. However, the effect of lignocellulose on aerobic granular sludge (AGS) system is still unknown. In this study, two reactors were operated over 5 months to investigate the effect of lignocellulose on granulation process, structure stability and pollutants removal of AGS. The results indicated that lignocellulose not only promoted the secretion of tightly bound polysaccharide in extracellular polymeric substances, but also acted as skeletons within granules, thereby facilitating AGS formation, and enhancing structural strength. Lignocellulose imposed little effect on the removal efficiency of pollutants, with more than 95%, 99%, and 92% of COD, NH4 + -N, and PO4 3–P were removed in both reactors. However, it did exhibit a noticeable influence on pollutants conversion processes. This might be due to that the presence of lignocellulose promoted the enrichment of functional microorganisms, including Candidatus_Accumulibacter, Candidatus_Competibacter, Nitrosomonas, and Nitrospira, etc. These findings might provide valuable insights into the control strategy of lignocellulose in practical AGS systems.